Hypochondria and Emotional Balance among Infected and non-Infected Corona Virus Employee in Kurdistan Region (Raparin Journal of Humanities (RJH), 2025)
The Study aimed to identify the levels of Hypochondria and Emotional Balance among Infected and non-Infected Corona Virus Employees, and to Identify differences of each hypochondria and Emotional balance between infected and non-infected employees, as well as to show how hypochondria to be predicted through Emotional balance and corona virus infection?Study sample consisted (446) of ministry of health, and ministry of labor and social affaire employees, selected by cluster incidental style, after using two different scales and study survey, the result showed the low level of hypochondria and High level of Emotional Balance among whole employees and infected and non-infected employees as well. but the results showed the difference of hypochondria between infected and non-infected employees in favor of infected employees, while there is no differences of Emotional Balance between them, finally the results showed that the low Emotional Balance level and Corona Virus Infection can predict Hypochondria among employees.